1999
DOI: 10.1002/chin.199935015
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Disordered Structures of Rare‐Earth Scandoborates of the Huntite Family.

Abstract: Disordered Structures of Rare-Earth Scandoborates of the HuntiteFamily.-Single crystals of solid solutions of huntite-type scandoborates (Ln 1 ,Ln 2 )(Lu,Sc) 3 (BO 3 ) 4 (Ln 1 : La, Ce, Nd; Ln 2 : Nd, Gd, Y) are grown and subjected to detailed X-ray and crystallo-chemical analyses. An irregular and disordered structure of these solid solutions is established. -(KUZ'MICHEVA, G. M.; RYBAKOV, V. B.; NOVIKOV, S. G.; AGEEV, A. YU.; KUTOVOI, S. A.; KUZ'MIN, O. V.; Zh. Neorg. Khim. 44 (1999) 3, 352-366; Moskovskii go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This conclusion is based on certain effects observed in the diffraction patterns, which are characteristic of the OD structures: (i) a presence of diffuse areas along with the point ones; (ii) a presence of diffraction reflections of a high symmetry; (iii) a difficulty in determining a real space group; (iv) similar a and b unit cell parameters and a multiple c parameter (for classical polytypes), wherein, for the huntite family compounds, the b parameters are the same, and the a and c parameters can be represented as a linear combination of vectors. For example, the unit cell parameters of the huntite family structures with the space groups R 32 and C 2/ c are correlated as a C 2/ c = 0.666­( c R 32 2 + 0.75 b R 32 2 ) 1/2 , b C 2/ c = b R 32 , c C 2/ c = 0.666­(4 c R 32 2 + 0.75 b R 32 2 ) 1/2 …”
Section: Results and Discussionmentioning
confidence: 99%
“…This conclusion is based on certain effects observed in the diffraction patterns, which are characteristic of the OD structures: (i) a presence of diffuse areas along with the point ones; (ii) a presence of diffraction reflections of a high symmetry; (iii) a difficulty in determining a real space group; (iv) similar a and b unit cell parameters and a multiple c parameter (for classical polytypes), wherein, for the huntite family compounds, the b parameters are the same, and the a and c parameters can be represented as a linear combination of vectors. For example, the unit cell parameters of the huntite family structures with the space groups R 32 and C 2/ c are correlated as a C 2/ c = 0.666­( c R 32 2 + 0.75 b R 32 2 ) 1/2 , b C 2/ c = b R 32 , c C 2/ c = 0.666­(4 c R 32 2 + 0.75 b R 32 2 ) 1/2 …”
Section: Results and Discussionmentioning
confidence: 99%
“…For the above-mentioned compounds, positional parameters have been refined only [90]. [35,76,82,83,85,89,91] and [35,84,86,87,91], respectively, and in the present work. To reduce an error associated with an absorption, the XRD data were collected over the entire Ewald sphere.…”
Section: Methodsmentioning
confidence: 99%
“…Resuts of XRD study of the Czochralski-grown single crystals and solid solutions ("Enraf-Nonius" CAD-4 single-crystal diffractometer; room temperature; AgK α , MoK α or CuK α ; size,~0.1 × 0.1 × 0.1 mm 3 ) with the initial compositions LaSc 3 (BO 3 ) 4 , CeSc 3 (BO 3 ) 4 , Pr 4 , performed by our scientific group, are given in [35,76,82,83,85,89,91] and [35,84,86,87,91], respectively, and in the present work. To reduce an error associated with an absorption, the XRD data were collected over the entire Ewald sphere.…”
Section: Space Groups For the Lnm 3 (Bo 3 )mentioning
confidence: 99%
“…Beregi et al [97] concluded that the starting crystallization temperature is a dominant factor in formation of the trigonal and monoclinic symmetry: for the phase with the nominal composition Eu 0.02 Tb 0.12 Gd 0. 86 Rare-earth scandium orthoborates, unlike other huntite-family rare-earth borates, exhibit a slightly different structural behavior. For example, for the LaSc 3 (BO 3 ) 4 , three modifications are known: a low-temperature (space group Cc, is a subgroup of the space group C2/c and it is absent for other rare-earth orthoborates), a medium-temperature (space group R32; as was mentioned above, this group is denied by many researchers) and a high-temperature (space group C2/c) ones.…”
Section: Crystallochemical Features Of the Huntite Familymentioning
confidence: 99%